2009
DOI: 10.1016/j.dam.2009.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Enumerating edge-constrained triangulations and edge-constrained non-crossing geometric spanning trees

Abstract: In this paper we present algorithms for enumerating without repetitions all triangulations and non-crossing geometric spanning trees on a given set of n points in the plane under edge inclusion constraint (i.e., some edges are required to be included in the graph). We will first extend the lexicographically ordered triangulations introduced by Bespamyatnikh to the edgeconstrained case, and then we prove that a set of all edge-constrained non-crossing spanning trees is connected via remove-add flips, based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In this section, we first introduce some notation used throughout the paper and then provide a number of preliminary results on the F -constrained lexicographically largest triangulation (F -CLLT). These results were originally obtained in [21] for the purpose of developing an efficient enumeration algorithm for edgeconstrained non-crossing spanning trees and play a crucial role in the development of our framework.…”
Section: The Edge-constrained Lexicographically Largest Triangulationmentioning
confidence: 96%
See 4 more Smart Citations
“…In this section, we first introduce some notation used throughout the paper and then provide a number of preliminary results on the F -constrained lexicographically largest triangulation (F -CLLT). These results were originally obtained in [21] for the purpose of developing an efficient enumeration algorithm for edgeconstrained non-crossing spanning trees and play a crucial role in the development of our framework.…”
Section: The Edge-constrained Lexicographically Largest Triangulationmentioning
confidence: 96%
“…For some specific graph classes, Avis et al [9] and the authors [21] have shown how to avoid duplicate generation based on a well-known enumeration framework, called the reverse search [6,7]. In this paper we extend this idea and develop a new general technique which does not rely on the property of a particular graph class.…”
mentioning
confidence: 95%
See 3 more Smart Citations